Impact of Dry Eye Syndrome on Vision-Related Quality of Life - Miljanović, Biljana; Dana, Reza; Sullivan, David A.; Schaumberg, Debra A. (American journal of ophthalmology, 2007)
To evaluate the impact of dry eye syndrome (DES) on vision-associated quality of life. Cross-sectional study. We identified 450 participants in the Women’s Health Study (WHS) and 240 participants in the Physicians’ Health Study (PHS) and sent a supplementary questionnaire asking how much their everyday activities were limited by symptoms of dry eye and to what degree problems with their eyes limited them in reading, driving, working at the computer, their professional activity, and watching television. By design, one-third of study subjects had clinically diagnosed DES or severe symptoms and two-thirds did not. We used logistic regression to examine relationships of DES with reported problems with everyday activities in each cohort and pooled estimates using meta-analysis methods. Of the participants invited, 85% completed the supplementary questionnaire, including 135 WHS and 55 PHS participants with DES, and 250 WHS and 149 PHS participants without DES. Controlling for age, diabetes, hypertension, and other factors, those with DES were more likely to report problems with reading ([odds ratio] OR = 3.64, 95% [confidence interval] CI 2.45 to 5.40, P < .0001); carrying out professional work (OR = 3.49, 95% CI 1.72 to 7.09, P= 0.001); using a computer (OR = 3.37, 95% CI 2.11 to 5.38, P < .0001); watching television (OR = 2.84, 95% CI 1.05 to 7.74, P = .04); driving during the day (OR = 2.80, 95% CI 1.58 to 4.96, P < .0001); and driving at night (OR = 2.20, 95% CI 1.48 to 3.28, P < .0001). DES is associated with a measurable adverse impact on several common and important tasks of daily living, further implicating this condition as an important public health problem deserving increased attention and resources.